2017
DOI: 10.3892/mco.2017.1220
|View full text |Cite
|
Sign up to set email alerts
|

Association between periodontitis and prognosis of pancreatobiliary tract cancer: A pilot study

Abstract: Abstract. Several studies have indicated that periodontitis is a risk factor for cancer. However, the association between periodontitis and the prognosis of pancreatobiliary tract cancer remains unclear. The aim of this pilot study was to investigate the association between periodontitis and prognosis of pancreatobiliary tract cancer. A total of 22 patients diagnosed with pancreatobiliary tract cancer were analyzed. Oral health status, including severity of periodontitis, general health status and biochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…We report here two distinct, though linked mechanisms activated by the oral pathobiont P. gingivalis that may possibly promote oral and other cancers: (a) immunosuppression through induction of MDDSCs, predominantly dependent on the DC-SIGN targeting Mfa1 fimbriae and (b) oncogenic response, predominantly through the CXCR4-targeting FimA fimbriae. Several recent reviews discuss the various cancers associated with CP, including gastrointestinal, pancreatobiliary tract 50 and oral squamous cell carcinoma (OSCC) 4 , 51 , 52 . OSCC represents the sixth most common malignant tumor.…”
Section: Discussionmentioning
confidence: 99%
“…We report here two distinct, though linked mechanisms activated by the oral pathobiont P. gingivalis that may possibly promote oral and other cancers: (a) immunosuppression through induction of MDDSCs, predominantly dependent on the DC-SIGN targeting Mfa1 fimbriae and (b) oncogenic response, predominantly through the CXCR4-targeting FimA fimbriae. Several recent reviews discuss the various cancers associated with CP, including gastrointestinal, pancreatobiliary tract 50 and oral squamous cell carcinoma (OSCC) 4 , 51 , 52 . OSCC represents the sixth most common malignant tumor.…”
Section: Discussionmentioning
confidence: 99%
“…2 Research also has demonstrated that it is also related with other diseases ( e.g. , cancer, 3 cardiovascular diseases, 4 respiratory tract infection, type 2 diabetes and neurodegenerative diseases 5 ), and thus the study of periodontal pathogens has attracted people's attention in various research fields. 6,7…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologic studies have suggested that periodontitis is a serious risk factor for other systemic disorders, including pneumonia, 4,5 diabetes mellitus, 6,7 atherosclerosis 8,9 cardiovascular disease, 10 and cancer 11,12 . Periodontitis is also regarded as a risk factor for pregnancy complications, including preterm‐birth (PTB), 13 fetal growth retardation (FGR), 14,15 and pre‐eclampsia (PE) 16 .…”
mentioning
confidence: 99%